Urban vacancy and the decline of the consolidated central area in Bauru (SP) - Silva, Juliana Pete; Goulart , Jefferson Oliveira (Technical and Scientific Journal Green Cities, 2025)
Objective – This study aims to analyze the phenomenon of urban vacancy and the depopulation of the consolidated central area in Bauru (SP), Brazil. Methodology – A systematic literature review was conducted, engaging with authors who discuss the depopulation of central areas, along with the concepts and explanatory categories that originated the theoretical discussion on urban vacancy. Originality/Relevance – Indicators of urban vacancy have systematically increased across the country, resulting in a corresponding demographic decline in consolidated central areas. This trend is linked to the expansive real estate movement, the enlargement of urban perimeters, and new vectors of urban expansion. While this phenomenon has been widely studied in large metropolitan centers, there is a gap in understanding how these trends manifest in medium-sized cities and regional capitals classified as "B-level" (IBGE). For this reason, the study focuses in Bauru, a municipality in the central-western region in State of São Paulo. Results Although still in the data collection and methodological definition phase, the study indicates a direct relationship between territorial expansion interests and the deterioration and demographic decline of city centers, without the implementation of urban policies or instruments by the municipality to address the issue. Theoretical/Methodological Contributions – This is a case study at an original scale, focusing on a municipality classified as a "medium-sized city" and a B-level regional capital (IBGE). The criteria for identifying urban vacancy are based on IBGE Census data and water connection records from the Bauru Water and Sewer Department (DAE), the municipal authority responsible for sanitation services. Social and Environmental Contributions – This study reinforces the importance of urban planning in developing sustainable cities (ODS 11 of the New Urban Agenda) and discusses the challenges in fulfilling the constitutional principle of the social function of property, highlighting how socio-spatial segregation is intensified when urban vacancy is not confronting.